Optimization of management control systems: Roles of internal audit - Zainal Abidin, Nor Hafizah; Haron, Hasnah; Md Shahbudin, Amirul Shah (Universiti Sultan Zainal Abidin(UniSZA), 2017)
Business failures are often attributed to poor leadership quality, ineffective corporate culture and malfunction of the organizational policies and systems. The aim of the present study is to understand and provide evidence on linkages roles of internal audit in supporting and monitoring the effectiveness of the control systems – leadership, culture and systems – of an organization. Based on the results from the semi-structured interviews conducted with the internal audit practitioners, the study found that the contemporary internal audit practices facilitate the effectiveness and adequacy of the control systems. Eventually, internal audit optimise the effectiveness of leadership quality, corporate culture, organizational policies and systems by means of overseeing the adequacy of governance, risk management and control processes.